Exchange proteins directly activated by cAMP (EPACs): Emerging therapeutic targets. Issue 8 (15th April 2017) - Wang, Pingyuan; Liu, Zhiqing; Chen, Haiying; Ye, Na; Cheng, Xiaodong; Zhou, Jia
Graphical abstract: Abstract: Exchange proteins directly activated by cAMP (EPACs) are critical cAMP-dependent signaling pathway mediators. The discovery of EPAC proteins has significantly facilitated understanding on cAMP-dependent signaling pathway and efforts along this line open new avenues for developing novel therapeutics for cancer, diabetes, heart failure, inflammation, infections, neurological disorders and other human diseases. Over the past decade, important progress has been made in the identification of EPAC agonists, antagonists and their biological and pharmacological applications. In this review, we briefly summarize recently reported novel functions of EPACs and the discovery of their small molecule modulators. The challenges and future perspectives are also discussed.